2015
DOI: 10.2463/mrms.2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Pseudonormal Corticomedullary Differentiation of the Kidney Assessed on T<sub>1</sub>-weighted Imaging for Chronic Kidney Disease Patients with Cirrhosis

Abstract: Purpose: We investigated whether corticomedullary differentiation (CMD) increased to a pseudonormal appearance on T 1 -weighted magnetic resonance (MR) images in patients with chronic kidney disease (CKD) with cirrhosis compared with patients with CKD without chronic liver disease.Methods: We assessed CMD on T 1 -weighted MR images of 32 patients with CKD with liver cirrhosis and 32 age-matched patients with CKD without liver cirrhosis, grading CMD visualization as good, moderate, or poor. We calculated quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These findings are also in line with some qualitative assessments in the 1990s [ 40 , 41 ], but not with all [ 42 ], due to the fact that renal T 1 values are modulated by many confounders, such as the degree of fibrosis [ 29 ], comorbidities (e.g. liver cirrhosis) [ 43 , 44 ], the acquisition protocol (e.g. breathing motion) and fastening and hydration level [ 14 ], which all together seem to be responsible for the accomplished correlations in the envisioned quantitative studies at 1.5 and 3T.…”
Section: Renal T 1 Mappingsupporting
confidence: 79%
“…These findings are also in line with some qualitative assessments in the 1990s [ 40 , 41 ], but not with all [ 42 ], due to the fact that renal T 1 values are modulated by many confounders, such as the degree of fibrosis [ 29 ], comorbidities (e.g. liver cirrhosis) [ 43 , 44 ], the acquisition protocol (e.g. breathing motion) and fastening and hydration level [ 14 ], which all together seem to be responsible for the accomplished correlations in the envisioned quantitative studies at 1.5 and 3T.…”
Section: Renal T 1 Mappingsupporting
confidence: 79%
“…The relevance of the strong relationship of renal cortex T 1 to both disease severity and clinical outcomes is novel. Two studies, in patients with cirrhosis, have suggested changes in T 1 occur within the cortex of the kidney, but until now these studies have been based on signal intensity changes of T 1 -weighted images, 29,30 with no quantitative measures of T 1 relaxation times having previously being reported. These previous studies suggest that the mechanism and physiology of reduced renal cortex T 1 is decreased water content in the renal cortex due to renal hypoperfusion.…”
Section: Healthymentioning
confidence: 99%
“…MRI is an ideal imaging method to identify GCK, because T2-weighted imaging is highly sensitive to cystic lesions and T1-weighted imaging reflects renal function. [3,5,911,13] Indeed, its diagnosis was made easily by 2 investigators, because T2-weighted MRI showed numerous, uniformly small cysts located in the renal cortex, which may reflect cystic dilatation of Bowman capsule. [1,3,5] In addition, the assessment of CMD by T1-weighted imaging was concordant between them in almost all kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [14] have reported that CMD is increased in patients with LC and normal renal function. Yamada et al [13] have shown that in patients with LC, poor CMD reflects renal function, but good and moderate CMD do not. Therefore, in older patients with chronic liver diseases, the presence of GCK can indicate renal impairment even when good or moderate CMD is observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation